Myeloid Neoplasms With KMT2A or MYC Amplification Exhibit Distinct Cytogenomic and Molecular Features and Clinical Outcomes - Min Yang; Madhu Ouseph; Madhulatha Pantrangi; Yi Huang; Liming Bao (Archives of Pathology & Laboratory Medicine, 2026)
Context.— KMT2A (lysine methyltransferase 2A) and MYC (MYC proto-oncogene, bHLH transcription factor) amplifications are reportedly rare in myeloid neoplasms, and there is a lack of studies comparing KMT2A and MYC amplifications in myeloid neoplasms. Objective.— To compare the cytogenomic and mutational features and the clinical outcomes of myeloid neoplasms with KMT2A or MYC amplification, and to characterize 4 cases with co-amplification of KMT2A and MYC . Design.— This study characterized and compared the cytogenomic, molecular, and clinical features of a large cohort of myeloid neoplasms with KMT2A and/or MYC amplification. Results.— This cohort of 52 myeloid neoplasms included acute myeloid leukemias (n = 44), myelodysplastic neoplasms (MDS) (n = 6), and MDS/myeloproliferative neoplasms (n = 2). There were KMT2A amplifications (n = 35), MYC amplifications (n = 13), and co-amplification of KMT2A and MYC (n = 4). KMT2A amplifications were exclusively intrachromosomal (32 of 32; 100%), whereas MYC amplifications were mainly extrachromosomal (9 of 13; 69.2%). Compared to MYC amplifications, KMT2A amplifications exhibited greater genomic complexity and a higher prevalence of monosomal karyotype, 5q deletion, and 17p/ TP53 (tumor protein 53) deletion. TP53 mutations were most common in KMT2A amplifications, while TET2 (tet methylcytosine dioxygenase 2) mutations were most frequent in MYC amplifications. Microarray analysis showed oscillating copy number changes on chromosome 11, indicating chromoanasynthesis, in KMT2A -amplified myeloid neoplasms. Simple excision and chromothripsis are likely the mechanisms underlying MYC amplifications. Co-amplification of KMT2A and MYC was associated with older age, complex karyotype, 17p/ TP53 aberrations, and dismal outcomes. Myeloid neoplasms with KMT2A amplification showed a trend for shorter overall survival than those with MYC amplification ( P = .08). Conclusions.— Myeloid neoplasms with KMT2A or MYC amplification display distinct cytogenomic and molecular profiles and differ in clinical outcomes.